Experiences With Artificial Intelligence Among Students at the University of Linyi - Ma Yiqing (Ilmu Inovasi Nusantara, 2026)
The rapid integration of artificial intelligence (AI) into higher education has transformed students' learning practices, yet its pedagogical, cognitive, and ethical implications remain insufficiently examined, particularly in Chinese universities. While AI offers substantial potential to enhance learning efficiency and access to information, concerns persist about its impact on students' critical thinking, information accuracy, and the humanistic dimensions of education. This study aims to explore the benefits, challenges, and practical application opportunities of AI use among students at Linyi University, with particular attention to both academic and non-academic contexts. Employing a mixed-methods research design, the study involved 300 undergraduate and graduate students selected through stratified sampling. Quantitative data were collected via structured questionnaires to assess patterns of AI usage and perceived benefits, while qualitative data were obtained through semi-structured interviews to capture students' lived experiences, concerns, and expectations regarding AI integration. The findings reveal that AI significantly enhances learning efficiency, supports academic task completion, and facilitates personalized learning experiences. However, students expressed notable concerns that excessive reliance on AI may weaken critical thinking skills, reduce independent problem-solving, and increase the risk of misinformation. Furthermore, the study finds that AI applications have spontaneously expanded into non-academic areas of students' lives, yet they remain unable to replace the emotional support, moral guidance, and value-based education provided by teachers. Based on these findings, the study highlights the need for a balanced, regulated approach to AI adoption. It proposes a multi-stakeholder governance framework involving universities, educators, policymakers, and technology developers to ensure the sustainable integration of AI that harmonizes technological advancement with humanistic educational values